Productivity or employment: is it a choice? - De Michelis, Andrea; Estevão, Marcello; Wilson, Beth Anne (Washington, DC, 2013)
": Traditionally, shocks to total factor productivity (TFP) are considered exogenous and the employment response depends on their effect on aggregate demand. We raise the possibility that in response to labor supply shocks firms adjust efficiency, rendering TFP endogenous to firms’ production decisions. We present robust cross-country evidence of a strong negative correlation between growth in TFP and labor inputs over the medium to long run. In addition, when using instruments to capture changes in hours worked that are independent of TFP shocks, we find that cross-country increases in labor input cause reductions in TFP growth. These results have important policy implications, including that low productivity growth in some countries may partly be a side effect of strong labor market performance. By the same token, countries facing a declining workforce, say, because of aging, may see accelerating TFP as firms find better ways of employing workers."